Impact of arbuscular mycorrhizal fungi and compost on the growth, water status, and photosynthesis of carob (Ceratonia siliqua) under drought stress and recovery. (4th July 2022) - Boutasknit, Abderrahim; Baslam, Marouane; Anli, Mohamed; Ait-El-Mokhtar, Mohamed; Ben-Laouane, Raja; Ait-Rahou, Youssef; El Modafar, Cherkaoui; Douira, Allal; Wahbi, Said; Meddich, Abdelilah
Abstract: Biofertilizers have been reported to increase resistance of plants to drought. However, the effects of combination of arbuscular mycorrhizal fungi (AMF) with compost (C + AMF) on carob under drought and recovery have not been studied and remain poorly understood. The effects of C + AMF on the growth performance, physiological and biochemical traits of carob under drought and recovery was evaluated. The experiment was divided into two phases: (i) phase 1: half of the plants were well-watered (WW) and other half were subjected to drought stress (DS), and (ii) phase 2: rewatering the plants under DS (REC). Our findings showed that C + AMF promoted growth, nutrient content, and modified physiological and biochemical parameters in carob during the two phases. After recovery, water content, stomatal conductance, the maximum photochemical efficiency of PSII, photosynthetic pigments and plant uptake of mineral nutrients were significantly higher in shoots of C + AMF than in controls. Moreover, C + AMF reduced to a greater degree the accumulation of hydrogen peroxide and malondialdehyde content in C + AMF than in controls. It can be concluded that AMF combined with compost can successfully be applied as biofertilizers for improving the growth, physiological and biochemical parameters in carob during both DS and after REC.